PELATIHAN KEWIRAUSAHAAN BERBASIS PANGAN LOKAL DI KELURAHAN BENPASI KECAMATAN KOTA KEFAMENANU KABUPATEN TTU - Mardit N. Nalle; Achmad S.Maulana; Ody W.Matoneng; Carles Y.A Nalle; Rita Indrasti (Universitas Muhammadiyah Manado, 2022)
Utilization of local raw materials available in the market can be the basis for the development of entrepreneurship training activities at the Gembor Farmer Group in the Benpasi area. In the implementation of this activity, it is done by looking for several people who are members of farmer groups or communities in the area to join in developing these activities. This is done to provide knowledge to the community to take advantage of the existing potential so that the resulting product can be sold at a reasonable price at the consumer level and provide hope for an increase in demand for a product. One form of this entrepreneurship is by training to make some processed products or market snacks such as several kinds of cakes which can later be used for the sales process to consumers. This will have an effect on increasing the community's income if the price is sold in accordance with the costs incurred. This training program is carried out by providing a positive influence on knowledge for the community so that in the future they can also play a role in developing these activities.